Real-World Data from Turkey: Is Sofosbuvir/Ledipasvir With or Without Ribavirin Treatment for Chronic Hepatitis C Really Effective? - BİLGİN, HÜSEYİN; SİLİ, ULUHAN (AVES, 2021)
Background: In this study, we aimed to investigate the efficacy and safety of sofosbuvir-based therapies in the treatment of chronic hepatitis C in real-world clinical practice. Methods: Data from patients with chronic hepatitis C treated with SOF/LDV +/- RBV or SOF/RBV in 31 centers across Turkey between April 1, 2017, and August 31, 2018, were recorded in a nationwide database among infectious disease specialists. Demographics, clinical, and virological outcomes were analyzed. Results: A total of 552 patients were included in the study. The mean age of the patients was 51.28 +/- 14.2, and 293 (55.8%) were female. The majority had HCV genotype 1b infection (65%), 75.04% of the patients underwent treatment, and non-cirrhosis was present at baseline in 381 patients (72.6%). SOF/LDV +/- RBV treatment was given to 477 patients and 48 patients received SOF/RBV according to HCV genotype. The total SVR12 rate was 99% in all patients. Five patients experienced disease relapse during the study and all of them were genotype 2. In patients infected with HCV GT2, SVR12 was 77.3%. SVR was 100% in all patients infected with other HCV genotypes. All treatments were well tolerated by patients without causing severe adverse events. Side effects and side effects-associated treatment discontinuation rates were 28.2% and 0.4%, respectively. Weakness (13.7%) was the common side effect. Conclusion: The present real-world data of 525 patients with HCV genotypes 1, 1a, 1b, 3, 4, and 5 who underwent SOF/LDV +/- RBV treatment in Turkey demonstrated a high efficacy and safety profile. HCV GT2 patients should be treated with more efficacious treatment.
Keywords: Chronic hepatitis C; sofosbuvir; ledipasvir; sustained virological response; genotype; real-world data; SOFOSBUVIR PLUS RIBAVIRIN; GENOTYPE 1 INFECTION; TREATMENT-NAIVE; ANTIVIRAL THERAPY; HCV INFECTION; OPEN-LABEL; LEDIPASVIR; SAFETY; LEDIPASVIR/SOFOSBUVIR